Socio-demographic determinants of dietary choices and their impact on health in Spanish adults - Sandri, Elena; Cantín Larumbe, Eva; Capoferri, Michela; Cerdá Olmedo, Germán; Werner, Lisa Ursula; Vega-Bello, M. Jesús (Frontiers in Public Health, 2024)
BackgroundAlthough Spain has traditionally followed the Mediterranean diet, in recent years, changes have become noticeable in the food preferences of the population. These changes include adopting new diets and dietary trends, such as plant-based diets, intermittent fasting and raw food diets. These choices are influenced by cultural, social and socio-demographic factors, and their impact on health should be studied in detail.AimThe objectives of this research are: (1) to study the prevalence of different dietary patterns among the Spanish population, (2) to explore the dependence of dietary choice on socio-demographic factors, (3) to investigate the relationship between the social habits and lifestyle choices of the population and how it affects health.MethodsA descriptive cross-sectional study was carried out on the Spanish population. Using a questionnaire constructed and validated by the research team, socio-demographic data were collected and different nutritional, social and lifestyle habits of the targeted population were explored.ResultsA valid sample of 22,181 people was collected among which 17,573 (79.2%) people claimed to follow a Mediterranean dietary pattern, 1,425 (6.4%) people followed a plant-based diet, 365 (1.6%) people are vegans, 1,018 people (4.6%) practiced intermittent fasting, 252 (1.1%) people followed a raw food diet and 1,548 people (7%) claimed to follow other types of diets. The data show that younger people (18–25 years old) tend to adopt more often a plant-based diet than older people and that women tend to follow this type of diet more often than men. On the other hand, men seem to practice intermittent fasting more frequently. A higher tendency to practice a raw food diet was found among people living in villages than those living in cities. Moreover, some trends were found in different regions of Spain, with greater adherence to a plant-based diet in Catalonia, while intermittent fasting is more common in the Region of Murcia. Finally, the results indicate that individuals who pay attention to their diet and experiment with various dietary patterns are generally more health-conscious. This is reflected in their adoption of healthier behaviors, such as exercising more and reducing their intake of alcohol and sugary drinks.